The Impact of COVID-19 Pandemic on Respiratory Syncytial Virus Infection in Children - Jose Boris Trigueros Montes; Diego Montes; Andrew Miele; Won Baik-Han; Gagan Gulati; Lily Q. Lew (Pulmonary Medicine)
Conclusions: We observed a lower incidence of RSV infection and a lower rate of hospitalization for RSV during the COVID-19 pandemic. The second RSV season during the COVID-19 pandemic began earlier, lasted longer, and had a lower frequency. Older children with milder illnesses were affected most during this season. RSV epidemiology and disease burden were impacted by the COVID-19 pandemic and could have significant ramifications for its prevention and control strategies.